1955
DOI: 10.1152/ajplegacy.1955.182.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reserpine (Serpasil) and Hydralazine (Apresoline) on Experimental Steroid Hypertension

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1956
1956
1980
1980

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This led us to consider that the damage may be attributed to the rise in blood pressure. This is also supported by the observation of Gaunt,8) who has demonstrated that treatment of the DCA-treated rats with a depressor drug, hydralazine hydrochloride (apresoline), prevents vascular damage. The investigation by Byrom and Dodson 9) in which sudden strain placed on the arterial walls by repeated forced injections of Ringer's solution into the carotid artery produced focal necrosis of the small arteries of the kidney, must also be considered as an evidence to prove the causal relation between high arterial pressure and vascular damage.…”
Section: Hypertension As a Factor In Causing Necrotizing Vascular Damagesupporting
confidence: 54%
“…This led us to consider that the damage may be attributed to the rise in blood pressure. This is also supported by the observation of Gaunt,8) who has demonstrated that treatment of the DCA-treated rats with a depressor drug, hydralazine hydrochloride (apresoline), prevents vascular damage. The investigation by Byrom and Dodson 9) in which sudden strain placed on the arterial walls by repeated forced injections of Ringer's solution into the carotid artery produced focal necrosis of the small arteries of the kidney, must also be considered as an evidence to prove the causal relation between high arterial pressure and vascular damage.…”
Section: Hypertension As a Factor In Causing Necrotizing Vascular Damagesupporting
confidence: 54%
“…These studies lend support to the hypothesis that various injuries, including nephrosclerosis, predispose to human pyelonephritis and that pyelonephritis is superimposed upon hypertensive disease more frequently than is usually suspected. Others (3)(4)(5) have shown that reserpine and/or hydralazine, when given to rats with DCA-saline hypertension, will reduce blood pressure, delay or prevent renal and vascular pathological changes, and increase the average survival time. Masson, McCormack, Dustan and Corcoran (6) demonstrated a close association between blood pressure levels and the presence and character of the vascular lesions in rats with hydralazine-treated renal hypertension.…”
mentioning
confidence: 99%